Gegen Qinlian decoction prevents post-ERCP pancreatitis by regulating NLRP3 inflammasome-mediated pyroptosis - Cui, Yurong; Li, Jinxin; Cai, Mengqiang; Zhang, Yu; Zhao, Bing; Liu, Junying (Frontiers in Pharmacology, 2025)
ObjectivePost-ERCP pancreatitis (PEP) is a type of acute pancreatitis (AP) and the most common complication after ERCP. NLRP3 inflammasome-dependent pyroptosis is a key factor in the pathogenesis of acute pancreatitis. Gegen Qinglian decoction (GQD) is a traditional Chinese medicine formula that has the effects of clearing heat and detoxifying, and is now widely used in pancreatic diseases. We have clinically found that GQD can effectively prevent PEP. To explore its potential preventive mechanism, we conducted rat experiments.MethodsBefore modeling, GQD, indomethacin suppository, NLRP3 inhibitor, etc. were used for intervention, and the GQD used was qualitatively analyzed by UPLC-QTOF-MS/MS. Then, a PEP model was established by injecting contrast medium into the pancreatic and bile ducts of rats, an in vitro model was made by intervening with sodium taurocholate (STC) in AR42J cells. The severity of pancreatitis and the levels of NLRP3 inflammasome components were subsequently evaluated in vivo and in vitro.ResultsUPLC analysis of GQD identified 227 known metabolites. The expression of NLRP3, Caspase-1, and GSDMD in PEP model was significantly increased compared to the blank group, indicating the activation of NLRP3 inflammasome mediated cell pyroptosis during PEP occurrence. Prophylactic administration of GQD resulted in a reduction in the expression of NLRP3, Caspase-1, and GSDMD. Additionally, GQD significantly alleviated the pathological inflammation in the pancreas, and reduced levels of amylase and inflammatory cytokines. The GQD group, indomethacin suppository group, NLRP3 inhibitor group, and siRNA gene suppression group showed similar results.ConclusionGQD can effectively prevent PEP, and its primary mechanism may be related to the regulation of NLRP3 inflammasome-mediated pyroptosis. Provide theoretical basis for the use of traditional Chinese medicine in clinical practice to prevent diseases.